Avaliação dos efeitos de um novo doador de óxido nítrico, 2nitrato-1,3-di (dodecanóxi) propano (NDDDP), sobre o sistema vascular de ratos - Ramos Neto, Edmilson de Souza (2020)
Nitrates have played a key role in medical practice for approximately 130 years and are widely used in the treatment of cardiovascular disorders. Although its use is well established in the treatment of these diseases, the search for new organic nitrates has been the target of some research groups. The aim of this study was to characterize the pharmacological effects of a new organic nitrate, 2-nitrate-1,3-di (dodecanoxy) propane (NDDDP), synthesized from glycerin, on the vascular function of normotensive rats through in vitro studies. In isolated cranial mesenteric artery rings of rats pre-contracted with 1 µM phenylephrine (FEN), NDDDP (10-12 - 10-3 M) induced concentration-dependent vasorelaxation in the presence and absence of functional endothelium. All subsequent experiments were performed in the absence of the endothelium. The effect of NDDDP was reduced after contraction mediated by depolarizing KCl solution (60 mM) when compared to its effect by FEN contraction. The vasodilator response of the compound was also attenuated in the presence of hydroxycobalamin – HDX (30 µM), an extracellular NO scavenger, and 1H- [1,2,4] oxadiazolo [4,3-a] quinoxalin-1-one - ODQ (10 µM), a soluble guanylyl cyclase (sGC) inhibitor. In addition, the NDDDP-induced relaxing effect was reduced by a nonselective K+ channel blocker, tetraethylammonium - TEA (3 mM) and by selective K+ channel blockers such as: a) TEA (1 mM, BKCa); b) 4 - Aminopyrin - 4-AP (1 mM, Kv); and c) Barium Chloride – BaCl2 (30 µM, KIR). However, the effect was not altered in the presence of glibenclamide - GLIB (10 µM, KATP). After incubation for 30 minutes with NDDDP (10-4 and 3 x 10-5 M), vasorelaxation was reduced. The data suggest that the NDDDP vasodilator action occurs through NO generation, with consequent activation of sGC, and activation of the BKCa, Kv and KIR channels.